Development of a model to predict 10-year risk of ischemic and hemorrhagic stroke and ischemic heart disease using the China Kadoorie Biobank - Yang, S; Han, Y; Yu, C; Guo, Y; Pang, Y; Sun, D; Pei, P; Yang, L; Chen, Y; Du, H; Wang, H; Massa, MS; et al. (American Academy of Neurology, 2022)
Background and Objectives Contemporary cardiovascular disease (CVD) risk prediction models are rarely applied in routine clinical practice in China due to substantial regional differences in absolute risks of major CVD types within China. Moreover, the inclusion of blood lipids in most risk prediction models also limits their use in the Chinese population. We developed 10-year CVD risk prediction models excluding blood lipids that may be applicable to diverse regions of China.